Co-Metabolism Kinetics of Bioremediation of Lambda Cyhalothrin, Chlorpyrifos and Malathion Contaminated Loam Soil Using Bio-Slurry Microbes - J. K, Mbugua; P. A, Kinyua; D. N, Mbui; A. G, Waswa (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The indiscriminate use of insecticide in agricultural soils causes significant soil and water pollution and poses a serious threat to the global community. Degradation of these pollutants is therefore vital in pollution control. Microbial fuel cells have been employed in bio-remediation of organic pollutants due to its environmental friendliness and low cost. The occurrence of pesticides in soil has become a highly significant environmental problem, which has been increased by the vast use of pesticides worldwide and the absence of remediation technologies that have been tested at full-scale. In this study, bioremediation experiments were conducted at ambient temperature of 28-32 0C and pH 5.6-8.9 to investigate the effectiveness of the process in the clean-up of pesticide contaminated loam soils. The loam soil was assessed for macro and micro properties prior to the experiments in control procedures. A H-shaped double chamber microbial fuel cell was fabricated where the anodic chamber was loaded with 750 mL loam soil inoculated with 750 mL bio-slurry doped with 10 mL of 10 ppm lambda cyhalothrin, chlorpyrifos and malathion pesticide solutions. The cathodic chamber was loaded with 1500 mL distilled water. The setup was incubated for a 90 days’ retention time where voltage and current were recorded daily using a multi-meter. The degradation level was assessed using a GC-MS after sample extraction using standard QuEChERs method. The voltage generated from the pesticide doped loam soil showed an upward trend from day 0 to day 15 in lambda cyhalothrin and malathion and from day 0 to day 20 in chlorpyrifos and pesticide mixture after which constant readings were observed for three days with downward trends thereafter. The maximum generated voltage was 0.537 V, 0.571 V, 0.572 V and 0.509 V in chlorpyrifos, lambda cyhalothrin, malathion and pesticide mix (MCL) respectively. The bioremediation levels for chlorpyrifos and malathion were 65.80 % and 71.32 %, respectively while no detectable, lambda cyhalothrin was observed after day 60 of the study. This study concludes that bioremediation of lambda cyhalothrin, chlorpyrifos and malathion in Limuru loam soil can be achieved using microbial fuel cells.